Magnetic and transport studies of core–shell nanorods based on metallic oxide ferromagnet SrRuO3. (January 2016) - Zheng, M.; Li, X.Y.; Zhu, Q.X.; Li, H.R.; Shi, L.; Li, X.M.; Zheng, R.K.
Abstract: This study presents the synthesis of perovskite metal-semiconductor core–shell heterostructures by sputtering SrRuO3 (SRO) shell layer on vertically aligned hydrothermally produced ZnO nanorods. Compared to the two-dimensional SRO films, the magnetic behaviors of the SRO shells on ZnO nanorods are morphology and thickness dependent, as reflected by the magnetic isotropy effects and the appearance of double-step magnetic hysteresis loops caused by nanograin-induced disorder and uncompensated spin at the surface and interface. The appearance of low-temperature resistance minimum and the good fitting of the low-temperature resistance data to a theoretical model establish the emergence of weak localization effect in the SRO shells, whose strength can be reinforced by a magnetic field. In addition, an apparent low-resistance Ohmic contact was realized in the ZnO/SRO heterojunctions due to the lower work function of the SRO. This, together with the absence of the Schottky barrier at the interface, demonstrates that the ZnO/SRO nanostructures could hold great promise for applications in advanced electron field emitters. Graphical abstract: Ohmic contact has been achieved for ZnO/SrRuO3 core–shell heterojunctions prepared by sputtering SrRuO3 shell layer on vertically aligned hydrothermally produced ZnO nanorods, which also show interesting phenomena such as weak localization effect and double-step magnetic hysteresis loops at low temperatures. Highlights: ZnO/SrRuO3 core–shell nanorods have been fabricated via a combination process. The core–shell nanorods show magnetic isotropy behavior. The core–shell nanorods show nanograin-induced double-step magnetic hysteresis loops. Magnetic field could enhance the weak localization effects in SrRuO3 shells. The ZnO/SrRuO3 heterojunctions show an Ohmic behavior of the resistance.